Numerical simulation study on multi-layer combined exploitation of natural gas hydrate reservoirs - YANG Zuoya,WU Xiaomin (Youqicang pingjia yu kaifa)
Offshore natural gas hydrate reservoirs are often accompanied by a large amount of free gas. However, the low permeability of the reservoir limits the flow of gas and water in different layers. Therefore, the fully exploitation of the hydrate-dissociation gas and free gas in the reservoir is the key to improve gas production efficiency. Based on the actual geological data in the Shenhu area of the South China Sea, the TOUGH+HYDRATE code is used to establish the numerical model of the combined exploitation of three different hydrate reservoirs with vertical wells. The spatial changes of gas production, water production, temperature, pressure field and hydrate saturation are analyzed, and then the optimized depressurization production strategy of natural gas hydrate is put forward. The results show that during the depressurization production, gas and water are continuously collected to the production well, and the temperature and pressure around the well drop rapidly. After continuous production for ten years, the water production rate continues to increase with the decrease of gas production rate. The cumulative gas production of three-layer combined mining method is up to 4.59×106 m3, and the cumulative water production is 8.31×105 m3. Hydrate dissociation is controlled by the depressurized gradient, hydrates around the well are preferentially dissociated, and the flow of underlying water will accelerate the dissociation of reservoir hydrates.